Tabiat kariasali: The affiliative leadership of the informal taumaas of the suluk communities on the east coast of Sabah - Nurhasan Danial; Asmiaty Amat; Nelson S. Dino; Nagder J. Abdurahman (University of Southeastern Philippines, 2024)
The taumaas (headman), as the nakura’ (leader) and a sara’ (lawgiver) of the adat (customs) appointed by the udduk hula’ (permanent resident), is the informal leader following the customs and traditions to exercise traditional authority over the Suluk communities. This study explores the tabiat kariasali (instinctual role) of the informal taumaas leadership in the Sabah East Coast Suluk communities, which uses a unique form of community leadership that addresses different community needs, including emotional well-being, spiritual harmony, social vices, educational needs, and healthcare. Through interviews with the nine taumaas in Semporna, Lahad Datu, and Sandakan in Sabah, the study reveals the strengths of the taumaas system. Thematic analysis of the responses highlights these leadership strengths, promoting social harmony through traditional mediation methods and integrating nasihat (religion) and governance to address emotional and spiritual needs while utilizing flexible collaboration and transformative justice approaches to combat social vices. Additionally, the creativity of the taumaas system is demonstrated through community-based literacy programs and the integration of traditional healing and healthcare practices in the Suluk community. However, the study also finds that the challenges they face, particularly in securing funds to sustain essential programs and the responsibilities of the taumaas, encompassing conflict resolution, education, and healthcare, create tension given limited financial resources. The official acknowledgment and support from the authorities would significantly enhance the informal leader’s endeavors to uphold peace and order and advance human development and cultural preservation. It is hoped that this study could explore potential solutions to resource constraints and investigate how the system can adapt when challenges arise in the Suluk community